Nanocredit programmes: when microcredit is too big / Zuraidah Mohamed Isa, Dahlia Ibrahim and Zaiful Affendi Ahmad Zabib - Mohamed Isa, Zuraidah; Ibrahim, Dahlia; Ahmad Zabib, Zaiful Affendi (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
One of the most inventive strategies for poverty reduction is a microcredit programme. Despite the fact that there is a significant body of literature describing the positive and significant effects of microcredit programmes on participants' lives, there are also a number of publications arguing that microcredit programmes have a negative effect on participants' lives. Some of the complaints included how microcredit programmes have caused participants to acquire dependency disorders, as well as how high interest rates and administrative fees have financially burdened them. In reality, critics of microcredit programmes on indebtedness have said that these programmes have led to some participants falling into a debt trap, leading to the problem of loan sharks.